Short-Term Effects on Diversity and Biomass on Grasslands from Artificial Dykes under Grazing and Mowing Treatments - Moinardeau, Cannelle; Mesléard, François; Ramone, Hervé; Dutoit, Thierry (Environmental conservation, 2019)
Few studies document the impacts of conservation management practices such as extensive grazing or mowing on the new ecosystems created by industrial conversions. In southern France, the Rhône channelling led to the construction of dykes to protect the Tricastin industrialized area from floods. Aiming to control plant dynamics for safety reasons and to favour plant biodiversity, mowing or extensive grazing by cattle were recently tested. Monitoring from both permanent plots and aerial photographs shows that three years of extensive grazing and annual mechanical mowing have modified plant composition, significantly increasing plant species richness, evenness and heterogeneity. The increase in evenness and beta-diversity from grazing was significantly higher than from mowing. Only grazing was able to reduce the height and cover of the dominant tussock perennial grass species (Brachypodium phoenicoides), while increasing bare soil cover and thus the contribution of annual species. The Normalized Difference Vegetation Index (NDVI) obtained through aerial photographic analyses confirmed the correlation between NDVI, aboveground biomass and plant species richness for the grazed site alone, allowing the results obtained from quadrats to be generalized to the scale of the grazed site. On the Rhône’s artificial dykes, extensive grazing appears to be a better management tool than mowing to enhance plant biodiversity and meet safety objectives.